Sassanian succession struggles : an analysis of the legitimisation practices of early seventh century Sassanian rulers in comparison with their predecessors - Vollgraaff, Carel Stephanus (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.